Cardiovascular health risk posed by polycyclic aromatic hydrocarbon and ultrafine particles. - Asweto, Collins O. (My University, 2018)
There is increased cardiovascular disease incidence attributed to ambient air pollution. It is estimated that ischaemic heart disease and stroke account for 80% of ambient air pollutionrelated early deaths. The most deleterious are the ultrafine particles (UFPs) which have more prominent potential health threat, since they can act as carriers of other strong air pollutant such as polycyclic aromatic hydrocarbons (PAHs). UFPs are small in size, hence can easily penetrate and reach cardiovascular tissues and organs. To understand their mechanisms, studies on UFPs and PAHs induced cardiovascular diseases were reviewed. The studies showed that UFPs and PAHs initiate events in atherogenesis including oxidative stress, expression of cell adhesion molecules on the surface of the endothelium, inflammation, and endothelial dysfunction. Endothelial dysfunction is associated with cardiovascular diseases such as hypertension, coronary artery disease, chronic heart failure, and peripheral vascular disease. The current review provides useful information on deleterious effect of UFP and PAH exposure on cardiovascular system. Thus advancing knowledge on UFP and PAH toxicity underscores the importance of the cardiovascular effects of air pollutants.
Keywords: Ultrafine particles; cardiovascular; endothelial dysfunction